2020
DOI: 10.1002/ajmg.a.62045
|View full text |Cite
|
Sign up to set email alerts
|

Stargardt misdiagnosis: How ocular genetics helps

Abstract: Ocular Genetics at Wills Eye Hospital sees a wide range of rare disorders for accurate diagnosis. To demonstrate how focused consultation and genetic testing results in precise diagnoses, we investigated false diagnosis rates for patients referred with a diagnosis of Stargardt disease. This is a retrospective review of patients over a 3 year period referred to our Ocular Genetics clinic for possible Stargardt disease, or already holding a diagnosis of Stargardt disease. Results of diagnostic and genetic testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…It has been thought that NIR-AF can better delineate the degree of RPE atrophy [ 12 ] ( Figure 1 and Figure 2 ). The full-field electroretinogram is usually normal or minimally abnormal, whereas multifocal electroretinogram (mf-ERG) may show a more demonstrable reduction of central retina responses [ 6 ].…”
Section: Fundus Autofluorescence and Near Infrared Autofluorescencementioning
confidence: 99%
See 3 more Smart Citations
“…It has been thought that NIR-AF can better delineate the degree of RPE atrophy [ 12 ] ( Figure 1 and Figure 2 ). The full-field electroretinogram is usually normal or minimally abnormal, whereas multifocal electroretinogram (mf-ERG) may show a more demonstrable reduction of central retina responses [ 6 ].…”
Section: Fundus Autofluorescence and Near Infrared Autofluorescencementioning
confidence: 99%
“…testing, is warranted for appropriate genetic counselling, prognostic information, and clinical trials due to the fact of emergent gene therapies [6].…”
Section: Fundus Autofluorescence and Near Infrared Autofluorescencementioning
confidence: 99%
See 2 more Smart Citations
“…For ABCA4R, the commonest phenocopy is the pattern dystrophy caused by variants in PRPH2 inherited in an autosomal dominant manner [70]. Indeed, Ibanez et al recently found that a PRPH2 variant was identified in 10% of their misdiagnosed STGD1 patients [71]. The typical phenotype linked to PRPH2 is a late-onset pattern dystrophy with variable penetrance within families.…”
Section: Clinical Phenotypes and Phenocopies In Abca4 Retinopathies (Abca4r)mentioning
confidence: 99%